Risk of mortality and second malignancies in primary myelofibrosis before and after ruxolitinib approval. (January 2022) - Thomas, John W.; Jamy, Omer; Shah, Mithun Vinod; Vachhani, Pankit; Go, Ronald S.; Goyal, Gaurav
Highlights: The survival of patients with MF may not have improved in the years following ruxolitinib approval. The incidence of second primary malignancies was higher in the post-ruxolitinib era. There was a higher incidence of AML transformation in the post-ruxolitinib era. Despite significant advances in our understanding of the molecular biology of MF, prognosis remains poor. Abstract: Background: Primary myelofibrosis (PMF) is associated with morbidity and mortality. Ruxolitinib gained US FDA approval for treatment of intermediate/high-risk PMF in November 2011. We evaluated differences in survival and second primary malignancy (SPM) incidence among US PMF patients in the years before and after ruxolitinib approval. Methods: We conducted a retrospective study utilizing the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER)-18 database for PMF patients. We divided patients into five-year cohorts pre- (2007−2011) and post-ruxolitinib (2012−2016) approval and compared relative survival rates (RSRs) to the standard population and standardized incidence rates (SIRs) of SPMs between cohorts. Results: We included 2020 patients diagnosed with PMF from 2007−2016 in this study. There was no difference in the four-year RSRs between cohorts (54 % vs. 57 %, p = 0.776). More patients developed SPMs in the post-ruxolitinib cohort (8% vs. 6%, p = 0.041). The majority of SPMs were hematologic with higher incidence of AML transformation in the post-ruxolitinib cohort (SIR 125.29 vs. 70.55). Conclusions: PMF prognosis remains poor in the years following ruxolitinib's approval. SPM incidence including AML transformation is higher in the years after approval. Further studies are needed to determine the true impact of ruxolitnib on population outcomes.